Geology and structural controls of lode-gold mineralisation around the Navachab Gold Mine in the Pan-African Damara Belt of Namibia - Creus, Pieter Koenraad (Stellenbosch : Stellenbosch University, 2011)
Thesis (MSc)--Stellenbosch University, 2011.